Derivation of a condition for the normal gain behavior of pyramidal horns. - Selvan, K.T.
The pyramidal horn exhibits a normal monotonically increasing gain versus frequency characteristic, only when its axial length is more than a certain minimum value for given aperture dimensions. In this letter, approximate equations are derived for estimating this minimum axial length
Keywords: Aperture dimensions; Approximate equations; Gain-frequency characteristic; Minimum axial length estimation; Monotonically increasing gain; Normal gain behavior; Pyramidal horns